ENGLISH INSTRUCTORS’ ROLES IN FOSTERING LEARNER AUTONOMY TO NON-ENGLISH DEPARTMENT STUDENTS - Eva Fauziah; Nenden Lengkanawati; Gin Gin Gustine (Edusentris, 2022)
The teacher's primary task as an education agent is to enhance and optimize the quality of student learning. It requires teachers to foster learner autonomy (LA) to think creatively, collaborate, be confident, be responsible, and become leaders. This study purposed to investigate the role of English instructors in fostering learner autonomy (LA) for non-English majoring students, the problems they face, and their responses to the solutions. This research employed a qualitative method. The data were collected through a questionnaire given to 30 English instructors and interviews with three instructors at the language center of a university in Indonesia. The results revealed that the instructors encouraged LA to teach non-English students English. The majority of them were often facilitators, counselors, resources, and managers in the classroom. They continued to manage autonomous learning despite obstacles in developing LA. The solution to their problem was attending training to promote LA. Therefore, this research is expected to provide a clear picture of the teacher's role in fostering student autonomy and provide teachers with an understanding of common problems and solutions to improve and optimize students' learning.